Potencial energético da madeira de Eucalyptus urophylla em função da idade e de diferentes materiais genéticos - Loureiro, Breno Assis (2021)
The objective in the present work was to evaluate age effect on wood quality characteristics, in addition to the yield and quality of charcoal produced by Eucalyptus urophylla hybrid clones, at six different ages (1, 2, 3, 4, 5 and 6 years), as well as to determine the relationship between the wood characteristics with those of charcoal. Basic density and higher calorific value (HCV) were determined. Chemical (extractives, lignin, holocellulose, syringyl/guaiacyl of lignin ratio, ash, elemental analysis), thermal (thermogravimetric analysis) and anatomical (individualization of fibers to determine cell wall thickness and wall fraction) analyzes were performed on the wood. The charcoal was produced in a muffle furnace, with 60°C.h-1 heating rate. The carbonization started at a temperature of 100°C to a maximum temperature 380°C, with a residence time of 60 minutes. In the charcoal produced, the gravimetric yields were determined, as well as the apparent relative density (ARD), immediate and elemental chemical analysis, higher calorific value (HCV). Basic and energetic density, dry mass and extractive content increased with tree age. Wood characteristics, such as holocellulose, ash, and nitrogen content had their values decreased with plant age. The TG/DTG curves showed three ranges of thermal decomposition, attributed to wood drying and to the hemicelluloses and cellulose decomposition. Higher gravimetric yield in charcoal, apparent relative density and energetic, fixed carbon content and energy efficiency were found in the more mature material. Specific wood consumption values, volatile material content, ash and nitrogen in charcoal reduced with age. The canonical correlations were high, and at three ages, the first and second pairs were significant at 15% probability. Tree age influenced the wood properties, although most clones showed satisfactory properties for the charcoal production for steel use, as a rule the more mature material had better performance. The ideal cutting age for energy purposes is 4 years since the wood and charcoal characteristics are similar to those most mature material, which can reduce forestry production costs and guarantee economic returns in a short period of time.